“Illegal” Gold Mining Operations in Ghana: Implication for Climate-Smart Agriculture in Northwestern Ghana - Yiridomoh, Gordon Yenglier (Frontiers in Sustainable Food Systems, 2021)
Globally, climate smart agriculture is highly recognized as an approach for sustainable agriculture and food systems. In Africa and other developing countries, climate smart agriculture is observed to reposition and modify agricultural systems for improved food and nutritional security. Despite the relevance of the approach to sustainable agricultural planning, illegal gold mining in many parts of the society is placing constraints to its implementation and adoption through its contest with agricultural land for space and activities. Illegal gold mining is on the rise due to the lucrativeness of the non-regulated gold rush opportunities with hard consequences on sustainable agriculture and resilience food systems. As result, this study seeks to investigate illegal gold mining and its environmental implication for climate smart agriculture in Ghana. The study employed a single case study using a mixed method approach to research. The study adopted purposive and systematic sampling techniques to select the study communities and respondents respectively. Questionnaire and interviews were used to gather the primary data from respondents at the household level, as the unit of analysis. Descriptive statistics and thematic analysis reveal that known agricultural practices such as terracing, crop rotation, use of domestic waste/manure, irrigation of crops were affected adversely by activities of illegal mining. The study recommends the need for conscious efforts from the Ministry of Lands and Natural Resources to sustain the ban on illegal mining with intensified monitoring and supervision while a systematic scheme involving relevant stakeholders is developed and implemented to ban illegal mining in Ghana completely. The Ministry of Food and Agriculture needs to develop an approach to support the adoption of climate smart agricultural practices by smallholder farmers to meet their households’ food demand. Keywords: Illegal mining, sustainable agriculture, environmental sustainability, Climate-smart agriculture, food systems